A Childcare Registration System with Activity Log and Multilevel Authentication for Pusat Jagaan Tunas Husnina - Hussin, Nur Izzah; Mohd Foozy, Cik Feresa (Applied Information Technology And Computer Science, 2024)
A childcare registration system is a system that registers and manages the child’s personal information at Pusat Jagaan Tunas Husnina such as home address and their parent’s contact number. The reason this system is developed is that the existing registration process at Pusat Jagaan Tunas Husnina is using a manual method which is to fill in the form paper. This manual process will be prone to many human errors, is less secure and is time-consuming for the teacher, admin or other related people to access back the data. The PHP language and waterfall methodology are used as a methodology to develop this system. At the end of this project, a childcare registration system for Pusat Jagaan Tunas Husnina is able to register and manage the child’s data at their childcare with an applied multilevel authentication system.